ANALYSIS OF THE EFFECTIVENESS OF ENTERPRISE HOUSE RETRIBUTIONS ON INCREASING REGIONAL REVENUES IN BARRU DISTRICT - A.Ariyadi; A.Aminah; Muhammad, Mukmin (P3M Stia Al Gazali Barru and Meraja media, 2022)
[Full Paper] to pdf Copyright (c) 2022 Meraja journal